2012
DOI: 10.1007/s00299-012-1274-4
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death is responsible for replaceable bud senescence in chestnut (Castanea mollissima BL.)

Abstract: This paper first reported the occurrence of programmed cell death during the senescence of vegetative buds in a woody species, and the results extend the range of knowledge of PCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Caspase-like proteases can be divided into three classes: metacaspases, vacuolar processing enzymes (VPEs), and saspases (Zhan et al [2012]). Some studies showed that saspases were involved in the proteolytic degradation of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) in biotic and abiotic PCD, whereas phytaspase overproducing and silenced transgenics provide evidence that phytaspase regulates PCD during both abiotic (oxidative and osmotic stresses) and biotic (virus infection) insults (Vartapetian et al [2011]). To certify the types and the roles of caspase-like protease induced by Al in peanut root tips are next important research field.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-like proteases can be divided into three classes: metacaspases, vacuolar processing enzymes (VPEs), and saspases (Zhan et al [2012]). Some studies showed that saspases were involved in the proteolytic degradation of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) in biotic and abiotic PCD, whereas phytaspase overproducing and silenced transgenics provide evidence that phytaspase regulates PCD during both abiotic (oxidative and osmotic stresses) and biotic (virus infection) insults (Vartapetian et al [2011]). To certify the types and the roles of caspase-like protease induced by Al in peanut root tips are next important research field.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of PCD is relatively the same in animal and plant cells (Havel and Durzan 1996). PCD is directly linked with vacuolization, (deoxyribonucleic acid) DNA fragmentation, and cell shrinkage and chromatin condensation in both plants and animals (Papini et al 2011;Poór et al 2013;Wang et al 2012). Generally, PCD includes, through an apoptotic process, the degradation of DNA fragments from 50 to 200 kb.…”
Section: Introductionmentioning
confidence: 99%
“…PI flow cytometric assay has been widely used for the evaluation of apoptosis in different tissues 33 . Apoptotic nuclei appear as a broad hypodiploxd DNA peak, which was easily discriminable from the narrow peak of normal (diploid) DNA content in the red fluorescence channels as PI is capable of binding and labeling DNA 34 36 . FCM measurements was proven to be a quantitative technology to study PCD dynamics 37 .…”
Section: Discussionmentioning
confidence: 99%